Do you have a fixation with alcohol?. (2nd July 2022) - Yates, Laura
Abstract : Laura Yates discusses what types of wipes are most effective for surface decontamination in the dental practice. Aims & objectives: To inform readers about the different definitions in decontamination To explain why decontamination wipes have increased in popularity To explain the history and use of alcohol in dental decontamination To inform readers about why alcohol alone should not be used on heavily contaminated surfaces Learning outcomes: Readers will understand what role wipes play in the decontamination process and when they should be used Readers will understand the theory behind the use of alcohol in dental decontamination Readers will understand the different options for cleaning and disinfection of surfaces and be able to explain their choice of materials